Manajemen pendataan aset sekretariat daerah kabupaten Lombok Timur - Masbullah Masbullah; Salmi Yuniar Bahri (Penerbit Goodwood, 2021)
Purpose: This study aimed to see how the Asset Data Collection Management of the Regional Secretariat of East Lombok Regency is in accordance with the rules from start to finish and get a clear picture of the research topic. Research methodology: This study was qualitative research. The data technique was done by using documentation, field observation, document review, and interview. The collected data were then analyzed using data analysis theory by Miles and Huberman. Results: The results showed that the Regional Asset Data Collection Management in East Lombok Regency was in accordance with the Domestic Government Regulation No. 19/2016. However, the management of official vehicles was not yet effective and efficient. This can be seen from the management practices that still follow the scope contained in the regulation. Limitations: The weakness of this study is that most of the data cannot be obtained from primary sources but relies on secondary data or other people's information. Contribution: It is hoped that this research can be used as a reference used in further research. Furthermore, the research results are expected to provide an overview of how the regional secretariat asset data management can be used as material for evaluation and improvement in local government policymaking.